Transformación de semilla a grano de cacao bajo condiciones controladas de proceso como alternativa para la valorización poscosecha (2023)
Cocoa, a versatile crop with rich historical significance, continues to hold cultural, social, and economic value worldwide. Therefore, enhancing the quality of chocolates through controlled cocoa seed transformation is of utmost importance, particularly in the chocolate industry, where consumers expect products that exhibit exceptional sensory characteristics and functional properties inherent in the composition. The cocoa seed transformation under controlled process conditions is in continuous development and seeks to consolidate itself as an emerging technology that offers benefits over spontaneous fermentation. The controlled transformation serves as the central focus of the research presented in this doctoral thesis, aiming to understand how the quality of chocolate is influenced depending on the operational variables during the transformation. To reveal it, this research analyzes the physical, chemical, and sensory changes in cocoa seeds and chocolates throughout the process. Various analytical techniques, including spectrophotometry, chromatography, and microscopic techniques, such as confocal laser scanning and scanning electron microscopy, are employed. Additionally, mathematical modeling, multivariate analysis, and image analysis tools are used to enhance the analysis. The results reveal a differentiated effect of organic acids on the microstructure of cocoa seeds during processing. They also highlight the significance of the mass transfer phenomenon in conditioning the seeds to initiate desired chemical reactions. Moreover, the concentration of organic acid emerges as the operational variable with the most significant influence on the content of bioactive compounds and the color parameters exhibited by cocoa matrices, the metabolomic profile of cocoa beans, and the volatile compound and sensory profiles of chocolates, playing a crucial role in the development of sensory notes, such as fruity, nutty, or sweet characteristics. These findings provide valuable insights into optimizing cocoa processing techniques and developing alternative approaches based on the dynamics of quality-related compound formation. Furthermore, they provide valuable guidance for positioning and expanding the exportable national cocoa supply in the market segment focused on high-quality products.